Utilizing the spatial frequency domain imaging to investigate change in optical parameters of skin exposed to thermal‐hydrotherapy: Ex‐vivo study. Issue 5 (7th April 2022) - Abdelazeem, Rania M.; Hamdy, Omnia
Abstract: Hydrotherapy is a traditional clinical practice that has been widely used for pain relief. However, immersion in hot water influences skin's moisture and morphology. In this study, we investigate the physiological changes of ex‐vivo chicken skin immersed in hot water (at 40 and 50°C) via monitoring the change in its absorption and scattering properties using the spatial frequency domain imaging (SFDI) technique. The procedure started by calculating the modulation transfer function of the proposed imaging system over a range of spatial frequencies using a high‐resolution test target. Thereafter, structured illumination patterns at different spatial frequencies were projected onto the examined samples via a reflective phase‐only spatial light modulator using transmission and reflection modes. The transmission and reflection images were recorded using a digital camera to reconstruct the optical absorption and scattering parameters. Such parameters were calculated using Kubelka–Munk and lookup table methods. For system validation, the optical properties of two kinds of milk (skimmed and full cream), as reference samples, were reconstructed using the proposed SFDI system in the reflection mode via lookup table method. The results revealed an increase in the scattering coefficient of the skin samples immersed in higher water temperature, while the absorption coefficient values were nearly the same. Furthermore, the obtained results were validated using Monte‐Carlo method showing absolute errors that range from 0.004 to 0.057. In conclusion, the proposed system was presented to investigate the changes in ex‐vivo skin properties under thermal‐hydrotherapy in the context of measured changes in optical parameters.